2016
DOI: 10.1523/jneurosci.4452-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Activation Preserves Visual Motion Perception Despite Noise Interference of Human V5/MT

Abstract: When processing sensory signals, the brain must account for noise, both noise in the stimulus and that arising from within its own neuronal circuitry. Dopamine receptor activation is known to enhance both visual cortical signal-to-noise-ratio (SNR) and visual perceptual performance; however, it is unknown whether these two dopamine-mediated phenomena are linked. To assess this, we used single-pulse transcranial magnetic stimulation (TMS) applied to visual cortical area V5/MT to reduce the SNR focally and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 60 publications
3
48
0
Order By: Relevance
“…Yet, our Bayesian results without exception provided evidence against an effect of 1.5mg cabergoline (all BF incl < .7). This absence of an effect is further strengthened by the fact that other studies using different cognitive tasks have previously reported significant effects of cabergoline on task performance using a similar or an even lower dose of orally administered cabergoline (Broadway, Frank, & Cavanagh, 2018;Cavanagh et al, 2014;Fallon, Zokaei, Norbury, Manohar, & Husain, 2017;Frank & O'Reilly, 2006;Nandam et al, 2013;Yousif et al, 2016). These observations together argue for an interpretation in terms of a true null result.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, our Bayesian results without exception provided evidence against an effect of 1.5mg cabergoline (all BF incl < .7). This absence of an effect is further strengthened by the fact that other studies using different cognitive tasks have previously reported significant effects of cabergoline on task performance using a similar or an even lower dose of orally administered cabergoline (Broadway, Frank, & Cavanagh, 2018;Cavanagh et al, 2014;Fallon, Zokaei, Norbury, Manohar, & Husain, 2017;Frank & O'Reilly, 2006;Nandam et al, 2013;Yousif et al, 2016). These observations together argue for an interpretation in terms of a true null result.…”
Section: Discussionmentioning
confidence: 85%
“…Several lines of evidence suggest that the dopaminergic system, which MPH also targets, regulates the SNR of neural information processing; that is, it affects gain modulation principles (Li et al, 2001;Servan-Schreiber et al, 1990;Yousif et al, 2016;Ziegler et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Both the dopamine system (Li et al, 2001;Servan-Schreiber et al, 1990;Yousif et al, 2016;Ziegler et al, 2016) underlying the resolution of perceptual-attentional conflicts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations